Answer:
<h3>
It's about 365 cm²</h3>
Step-by-step explanation:
2×πr² + 2πr×h =
= 2×π×4² + 2π×4×10.5 =
= 32π + 84π =
= 116π ≈
≈ 364.42 cm²
Answer:
a=55
b=55
c=125
d=125
e=55
f=55
g=125
Step-by-step explanation:
Answer:
Y=K×X...... equation
When,Y=8 and X=-5
To find the constant (K)
we substitute for K in the equation
8=K×-5
8=-5K divide both sides by -5
8÷-5=-5K÷-5
K=-1.6
Answer:
![-\frac{x^2y^2}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7Bx%5E2y%5E2%7D%7B2%7D)
Step-by-step explanation:
We have an extremely large equation and are asked to divide it, so let's solve it step-by-step :
Remove the parenthesis to make it easier to read :
![\frac{-3x^3 *2x^3y^4z *3z^2}{4x^3z*3yz*3xyz}](https://tex.z-dn.net/?f=%5Cfrac%7B-3x%5E3%20%2A2x%5E3y%5E4z%20%2A3z%5E2%7D%7B4x%5E3z%2A3yz%2A3xyz%7D)
Multiply the numerators :
![\frac{-18x^6y^4z^3}{4*3*3x^3yyzzz}](https://tex.z-dn.net/?f=%5Cfrac%7B-18x%5E6y%5E4z%5E3%7D%7B4%2A3%2A3x%5E3yyzzz%7D)
Multiply the denominators :
![\frac{-18x^6y^4z^3}{36x^4y^2z^3}](https://tex.z-dn.net/?f=%5Cfrac%7B-18x%5E6y%5E4z%5E3%7D%7B36x%5E4y%5E2z%5E3%7D)
Apply the negative rule :
![-\frac{18x^6y^4z^3}{36x^4y^2z^3}](https://tex.z-dn.net/?f=-%5Cfrac%7B18x%5E6y%5E4z%5E3%7D%7B36x%5E4y%5E2z%5E3%7D)
Cancel the common factor which is 18 :
![-\frac{x^6y^4z^3}{2x^4y^2z^3}](https://tex.z-dn.net/?f=-%5Cfrac%7Bx%5E6y%5E4z%5E3%7D%7B2x%5E4y%5E2z%5E3%7D)
Apply the addition exponent rule :
![\frac{y^4z^3x^{6-4} }{2y^2z^3}](https://tex.z-dn.net/?f=%5Cfrac%7By%5E4z%5E3x%5E%7B6-4%7D%20%7D%7B2y%5E2z%5E3%7D)
Subtract :
![\frac{x^2y^4z^3 }{2y^2z^3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E2y%5E4z%5E3%20%7D%7B2y%5E2z%5E3%7D)
Apply the rule for y :
![\frac{x^2y^{4-2} z^3 }{2z^3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E2y%5E%7B4-2%7D%20z%5E3%20%7D%7B2z%5E3%7D)
Subtract :
![\frac{x^2y^2z^3 }{2z^3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E2y%5E2z%5E3%20%7D%7B2z%5E3%7D)
Cancel the common factor of z^3 :
![-\frac{x^2y^2}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7Bx%5E2y%5E2%7D%7B2%7D)
<u>Zeros of the function</u>
f(x) = (x + 2)² - 25
f(x) = (x + 2)(x + 2) - 25
f(x) = x(x + 2) + 2(x + 2) - 25
f(x) = x(x) + x(2) + 2(x) + 2(2) - 25
f(x) = x² + 2x + 2x + 4 - 25
f(x) = x² + 4x + 4 - 25
f(x) = x² + 4x - 21
x² + 4x - 21 = 0
x = <u>-(4) +/- √((4)² - 4(1)(-21))</u>
2(1)
x = <u>-4 +/- √(16 + 84)</u>
2
x = <u>-4 +/- √(100)
</u> 2<u>
</u>x = <u>-4 +/- 10
</u> 2<u>
</u>x = -2 <u>+</u> 5<u>
</u>x = -2 + 5 x = -2 - 5
x = 3 x = -7
f(x) = x² + 4x - 21
f(3) = (3)² + 4(3) - 21
f(3) = 9 + 12 - 21
f(3) = 21 - 21
f(3) = 0
(x, f(x)) = (3, 0)
or
f(x) = x² + 4x - 21
f(-7) = (-7)² + 4(-7) - 21
f(-7) = 49 - 28 - 21
f(-7) = 21 - 21
f(-7) = 0
(x, f(x)) = (-7, 0)
<u>Vertex</u>
<u>X - Intercept</u>
<u />-b/2a = -(4)/2(1) = -4/2 = -2
<u>Y - Intercept</u>
y = x² + 4x - 21
y = (-2)² + 4(-2) - 21
y = 4 - 8 - 21
y = -4 - 21
y = -25
(x, y) = (-2, -25)
<u />